Peran Guru dalam Menegakkan Disiplin Kelas - Titin Nurrohmat; Cibro, Desi Karunia; Wina Mustikaati (Publikasi dan UKI Toraja Press Universitas Kristen Indonesia Toraja, 2025)
Enforcement of discipline in the classroom is an important aspect in creating a conducive and productive learning environment. Teachers as classroom managers play a major role in shaping students' disciplinary behavior through educative, consistent, and humanist approaches. This article aims to examine the role of teachers in enforcing discipline in the classroom based on literature studies from various scientific sources. The method used is library research by collecting and analyzing relevant literature. The results show that effective discipline strategies involve open communication, instilling positive values, providing fair consequences, and creating harmonious student-teacher relationships. The main challenges faced by teachers include the diversity of student characters, time constraints, and lack of support from the school environment and parents. This study concludes that the role of teachers is crucial in building student discipline and needs to be supported by continuous training and supportive school policies. The implications of this study are expected to be a reference in the development of educational policies and improving teachers' pedagogical competencies in terms of classroom management.